Early Optical Follow-Up Observations of Einstein Probe X-Ray Transients During the First Year - Siyu Wu; Ignacio Pérez-García; Alberto J. Castro-Tirado; Youdong Hu; Maria Gritsevich; María D. Caballero-García; Rubén Sánchez-Ramírez; Sergiy Guziy; Emilio J. Fernández-García; Guillermo García Segura; Carlos Pérez-del-Pulgar; Dingrong Xiong; et al. (Galaxies)
We present early follow-up observations of Einstein Probe (EP) X-ray transients, following its first year of operation. EP is a dedicated wide-field X-ray observatory that is transforming our understanding of the dynamic X-ray universe. During its first year, EP successfully detected a diverse range of high-energy transients—including gamma-ray bursts (GRBs), tidal disruption events (TDEs), and fast X-ray transients (FXTs), besides many stellar flares, disseminating 128 alerts in the aggregate. Ground-based optical follow-up observations, particularly those performed by our BOOTES telescope network, have played a crucial role in multi-wavelength campaigns carried out so far. Out of the 128 events, the BOOTES Network has been able to follow up 58 events, detecting 6 optical counterparts at early times. These complementary optical measurements have enabled rapid identification of counterparts, precise redshift determinations (such as EP250215a at <semantics>z=4.61</semantics>), and detailed characterization of the transient phenomena. The synergy between EP’s cutting-edge X-ray monitoring and the essential optical follow-up provided by facilities, such as the above-mentioned BOOTES Global Network or other Spanish ground-based facilities we have access to, underscores the importance and necessity of coordinated observations in the era of time-domain and multi-messenger astrophysics.